2010
DOI: 10.1111/j.1365-2044.2010.06329.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect‐site concentration of remifentanil attenuating surgical stress index responses to intubation of the trachea

Abstract: SummarySurgical Stress Index has been proposed for assessment of surgical stress and analgesia. It is a numeric index based on the normalised pulse beat interval and photoplethysmographic pulse wave amplitude. We determined the effect-site concentration of remifentanil for attenuation of Surgical Stress Index responses to intubation of the trachea. Thirty ASA 1-2 patients received either deep or normal anaesthesia and then target-controlled remifentanil. Burst suppression was maintained in the deep group and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…There are many studies related to propofol-remifentanil TCI induction methods to suppress hemodynamic instability [13][14][15]. Albertin et al [13] suggested that EC50 of remifentanil during intubation is 5.0 ng/mL (95% CI, 4.7-5.4 ng/mL) while using Ce of propofol 4 µg/mL, which is similar to the results of our study in group PRO 3.5.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…There are many studies related to propofol-remifentanil TCI induction methods to suppress hemodynamic instability [13][14][15]. Albertin et al [13] suggested that EC50 of remifentanil during intubation is 5.0 ng/mL (95% CI, 4.7-5.4 ng/mL) while using Ce of propofol 4 µg/mL, which is similar to the results of our study in group PRO 3.5.…”
Section: Resultssupporting
confidence: 87%
“…Albertin et al [13] suggested that EC50 of remifentanil during intubation is 5.0 ng/mL (95% CI, 4.7-5.4 ng/mL) while using Ce of propofol 4 µg/mL, which is similar to the results of our study in group PRO 3.5. Mustola and Toivonen [14] suggested that EC50 and EC95 of remifentanil is 3.17 ng/mL and 3.79 ng/mL, respectively, during intubation while using Ce of propofol 4 µg/mL, and this study showed lower Ce compared with our group PRO 3.5. Troy et al [15] consider that a Ce of remifentanil 8 ng/mL along with a Ce of propofol 3 µg/mL may provide satisfactory conditions for intubation while avoiding major adverse effect, compared with our study in group PRO 3.5 in which EC95 was 5.42 ng/mL (95% CI, 5.13-7.47 ng/mL), showing a higher Ce.…”
Section: Resultssupporting
confidence: 41%
“…From these values, it generates a number on a linear scale (0–100), where values exceeding 50 are thought to represent pain. Most current research has investigated its ability to aid titration of intra‐operative remifentanil this response to noxious stimulation . Although pre‐clinical and clinical (intra‐operative and postoperative) research indicated its ability to discriminate strong noxious stimuli from no stimulation , the method could not consistently differentiate stimulus intensities .…”
Section: Resultsmentioning
confidence: 99%
“…Monitoring depth of analgesia is an on going challenge for anaesthetists [16, 17], and the SPI is a recent development in this field. Previously published data show that the variables measured by the SPI, namely the normalised heart beat interval and the pulse plethysmographic amplitude, are indeed capable of detecting noxious stimuli representing nociception [3], and are affected by analgesia representing anti‐nociception [4, 18, 19]. Apart from nociception, however, many other factors such as hypovolaemia, catecholamine levels, drugs affecting heart rate [10] and position may contribute to a patient`s ‘surgical stress’ and affect the surrogate variables measured by the SPI.…”
Section: Discussionmentioning
confidence: 99%